Digital Emergency Response, Process Reforms and Social Well-being in India: An Empirical Evaluation of ERSS/Dial 112 Under the Ease-of-living Framework - Alok Kumar Gaurav; Sunil Gupta; Utkarsh Mishra; Saurabh Yadav (Indian Journal of Public Administration, 2026)
Social well-being and democratic governance have safety and security as a fundamental dimension. Traditionally, policing responsiveness and emergency service shortages in India have negatively affected people’s safety, their confidence in various governmental institutions and the overall standard of living. Recognising this, the Government of India has progressively focused on process reforms and digital governance to improve service delivery and the citizen experience. In this article, the author discusses the Emergency Response Support System (ERSS), also known as Dial 112, as an approach to enhancing safety and security, a pillar of the ease-of-living (EoL) index. The author focuses on how ERSS operationalises incremental, nut-and-bolt administrative reforms based on standardisation and technological integration, as well as data-driven monitoring. The research is based on empirical methods within a mixed-methods approach, primary citizen opinion surveys and a particular case study of Uttar Pradesh, one of the most extensive implementations of Dial 112 in India. Across all key dimensions of service quality, the empirical results reveal generally high levels of citizen satisfaction. The mean scores were highest for responsiveness ( M = 4.30), followed by assurance ( M = 4.24), awareness ( M = 4.23) and overall reliability ( M = 4.22). A total of 85.9% of respondents agreed that emergency calls were answered promptly. In addition, regression analysis revealed that responsiveness (β = 0.31, R 2 = 0.69, p < .001), assurance (β = 0.26, R 2 = 0.69, p < .001) and reliability (β = 0.18, R 2 = 0.69, p < .001) were significant predictors of perceived EoL. The results show the potential of technology-based emergency response systems to foster institutional trust, create a sense of security and drive citizen-centric governance and public administration reforms in India.